(untitled) (Revista de Ciências Agroveterinárias, 2015)
Hyptis pectinata, belonging to Lamiaceae family, is used in northeastern folk medicine due to its phytotherapeutic properties for treatment of inflammation, bacterial infections, and pain. The objective of this work was to evaluate the influence of the cutting position of the branch and the composition of the substrates in the aerial and root development of H. pectinata plants. Cuttings were selected from the apical, median, and basal plants grown in the seed house of Garanhuns municipality, PE. Cuttings were propagated in different substrates (soil, manure, and soil + manure). Results showed that highest budding number occurred for basal cutting (4.45 un.) in the soil + manure substrate. The highest average number of roots occurred in cutting from the median and basal positions in the soil + manure substrate. The best substrate for the rooting of cuttings of H. pectinata is the soil associated with manure, and the cuttings from the median and basal positions are the most suitable for the vegetative propagation of this species.